2019
DOI: 10.3390/md17040239
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal and Antioxidant Properties of Chitosan Polymers Obtained from Nontraditional Polybius henslowii Sources

Abstract: Chitin was extracted from Polybius henslowii, a swimming crab, captured in large quantities throughout the Portuguese coast by purse seine vessels as bycatch. After standard chitin extraction procedures, water-soluble chitosan products were obtained via two different methods: (1) N-acetylation with the addition of acetic anhydride and (2) a reaction with hydrogen peroxide. The chemical structure and molecular weight of chitosan derivatives, water-soluble chitosan (WSC) and chitooligosaccharides (COS), were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(74 citation statements)
references
References 68 publications
2
72
0
Order By: Relevance
“…The physicochemical properties of chitosan end products can be modulated by controlling factors such as chitin source of origin, reaction conditions (concentration, ratios of chitin to alkali, temperature), and extent of the reaction. It is known that hydroxyl, and amino groups in chitosan are key components in eliminating anion radicals such as superoxide and hydroxyl radicals [8][9][10]12] It has been reported that the amino and hydroxyl groups on chitosan backbone represent target moieties for chemical modifications to improve the aqueous solubility of chitosan since it is soluble only in an aqueous acidic solution, which is a major hurdle for its application [5]. The unique properties of chitosan, such as nontoxicity to humans [13][14][15]; commercial accessibility, biodegradability and biocompatibility [14,15], and high mucoadhesive properties [15,16] make chitosan an excellent choice for nanoparticle assembly.…”
mentioning
confidence: 99%
“…The physicochemical properties of chitosan end products can be modulated by controlling factors such as chitin source of origin, reaction conditions (concentration, ratios of chitin to alkali, temperature), and extent of the reaction. It is known that hydroxyl, and amino groups in chitosan are key components in eliminating anion radicals such as superoxide and hydroxyl radicals [8][9][10]12] It has been reported that the amino and hydroxyl groups on chitosan backbone represent target moieties for chemical modifications to improve the aqueous solubility of chitosan since it is soluble only in an aqueous acidic solution, which is a major hurdle for its application [5]. The unique properties of chitosan, such as nontoxicity to humans [13][14][15]; commercial accessibility, biodegradability and biocompatibility [14,15], and high mucoadhesive properties [15,16] make chitosan an excellent choice for nanoparticle assembly.…”
mentioning
confidence: 99%
“…Peculiarly, XRD patterns for 10 kGy γ-ray-irradiated chitosan peaks at 2θ = 10.5°, 20.04°, and 21.9° with reflections were 20, 200, and 220 h, respectively. ( Figure 3 ), which was identical to non-irradiated chitosan [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. However, when the 20 kGy γ-ray was used, an additional peak developed at 2θ = 10.5°.…”
Section: Resultsmentioning
confidence: 56%
“…A 37.33% (for 10 kGy) and 72.12% (20 kGy) increase was witnessed for DPPH activity with respect to the untreated sample (0 kGy). It has been reported that the antioxidant activity of chitosan increases with the increase of irradiation doses and decreases the M W [ 21 ]. It was reported that one of the mechanisms of chitosan is related to its scavenging activity, which can respond with free radical leftover free –NH 2 groups to form stable molecules and the –NH 2 groups can form ammonium groups ( ) by capturing a hydronium ion from the solution [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies indicated that the molecular weight and the degree of deacetylation affect the biological activity of chitosan. The inhibition of phytopathogens is partial in both products with higher degrees of chitooligosaccharides deacetylation or low deacetylation-Water-soluble chitosan products at the highest evaluated concentrations [ 18 ].…”
Section: Discussionmentioning
confidence: 99%